Caladium Cultivars ‘Pink Panther’ and ‘Crimson Skye’ - Zhanao Deng; Natalia Peres; Johan Desaeger (EDIS, 2021)
Caladium is an ornamental aroid valued for its variably shaped bright foliage. Two new lance-leaved cultivars, ‘Pink Panther’ and ‘Crimson Skye’, were released in 2020 by the UF/IFAS caladium breeding program to meet the need for more lance-leaved cultivars. This new 9-page article is prepared for growers who are interested in growing caladium as a horticultural crop and for greenhouse or nursery growers who are interested in producing potted caladium plants.